2011
DOI: 10.1248/bpb.34.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chemical Modification of Ursodeoxycholic Acid on TGR5 Activation

Abstract: The aim of this study is to examine the ability of the bile acid analogues obtained by chemical modification of ursodeoxycholic acid (UDCA) for TGR5 activation. Eleven UDCA analogues including 3-or 7-methylated UDCAs and amino acid conjugates were investigated as to their ability to activate TGR5 by means of the luciferase assay. It was noteworthy that 7a a-methylated UDCA, namely 3a a,7b b-dihydroxy-7a a-methyl-5b b-cholanoic acid, had a significantly high affinity for and ability to activate TGR5 as compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…Second, OA -a potent TGR5 agonist that does not activate nuclear BA receptors (48) -was the strongest stimulant of excitability. Third, UDCA -which does not activate TGR5 or is a weak agonist (28,49), yet retains the irritant and detergent properties of BAs -had no effect on neuronal excitability at any concentration tested. The effects of DCA, TLCA, and OA on rheobase were concentration dependent, and, with the exception of TLCA, all agonists increased AP discharge frequency at the highest tested concentrations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, OA -a potent TGR5 agonist that does not activate nuclear BA receptors (48) -was the strongest stimulant of excitability. Third, UDCA -which does not activate TGR5 or is a weak agonist (28,49), yet retains the irritant and detergent properties of BAs -had no effect on neuronal excitability at any concentration tested. The effects of DCA, TLCA, and OA on rheobase were concentration dependent, and, with the exception of TLCA, all agonists increased AP discharge frequency at the highest tested concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…tic activity, while retaining the detergent and irritant properties of BAs (28,49). UDCA (30 or 100 μM, 10 minutes) did not affect rheobase, AP discharge frequency, resting membrane potential, or input resistance ( Figure 4E and data not shown).…”
Section: Figurementioning
confidence: 89%
“…Likewise, UDCA derivatives bearing a methyl group at the C3 position (23, 24) proved to be less active than the parent compound (Table 10.2). 56 Secondly, while the oxidation of the 3a-hydroxyl group led to the enhancement of the activity in CDCA (3) and LCA (1), its elimination or epimerization decreased the potency of the compound at the receptor (Table 10.2). 5 Interestingly, a different trend was observed in the case of UDCA derivatives, with either the epimerization or the oxidation proving detrimental for TGR5 agonist activity.…”
Section: Steroidal Ligands: Bile Acids Bile Alcohols and Derivativesmentioning
confidence: 99%
“…5 Interestingly, a different trend was observed in the case of UDCA derivatives, with either the epimerization or the oxidation proving detrimental for TGR5 agonist activity. 56 The authors ascribed this discrepancy to the presence of the 7b-hydroxyl group that might promote a different binding mode of the 3-dehydro-UDCA (25) to the receptor. The study of Sato et al showed that the introduction of alkyl groups in C7-b position of CDCA improved TGR5 agonist activity, with the potency being directly correlated with the size of the substituent (Table 10.2).…”
Section: Steroidal Ligands: Bile Acids Bile Alcohols and Derivativesmentioning
confidence: 99%
“…Structurally, TGR5 agonists can fall into two categories. The first category is bile acid derivatives, [10][11][12] such as lithocholic acid (LCA) and 6α-ethyl-23(S)-methylcholic acid (INT-777). The second category is non-bile acid derivatives, including naturally occurring non-bile acid agonists such as oleanolic acid and betulinic acid, 13,14) and synthetic small molecular TGR5 agonists.…”
mentioning
confidence: 99%